Teaser advertising as an instrument of marketing communications: overview - Soloviova, Yulia (My University, 2018)
The aim of study is to consider the conceptual features of advertising campaigns with the usage of a teaser. It is also important to emphasize the consideration of unsuccessful teaser messages as one of the components of modern provocative marketing.
Keywords: кафедра маркетингу; реклама; тизер; провокативний маркетинг; advertising; teaser